A New Cuii-Dinuclear Paddlewheel Complex. Structural and Electronic Properties - Venegas-Yazigi, D; Venegas-Yazigi, D (Elsevier B.V., 2021)
A new paddlewheel dinuclear CuII complex [Cu2(HL)4(MeOH)2](MeOH)4, Cu2-PW was obtained using the 3,5-di‑tert‑butyl‑salicylic acid as a ligand (H2L). The Cu2-PW crystallizes in the monoclinic P2/c space group having a Cu…Cu distance of 2.5727(17) Å. The hydrogen bonds between coordinated and solvate methanol molecules link the structure into a pseudo-one-dimensional array with a Cu…Cu interdimer distance of 9.180(5) Å. Temperature dependence of magnetic susceptibilities revealed a strong antiferromagnetic interaction between the two CuII ions (J = −323 cm−1). DFT calculations showed that the strong antiferromagnetic behavior is originated from magnetic orbital centered only on CuII cations and carboxy oxygen atoms, with a calculated exchange magnetic coupling constant of J12= -311 cm−1. Time-dependent calculations were also performed to characterize the main electronic transition involved in the two well-defined maxima observed in solid-state. The results show that the maximum at 695 nm corresponds to d-d and carboxylate intraligand transitions, while the maximum centered at 320 nm was assigned to phenyl to carboxylate ILCT transition. The shoulder located around 400 nm corresponds to MLCT transition from HL− ligand to CuII center. In our knowledge, this is the first time that a copper paddlewheel complex with the salicylic ligand is studied using the hole-electron method to give a univocal assignment for the UV–vis spectrum. © 2020